To solve the equation \(2x^3 - x^2 - 2x + 1 = 0\) using factoring by grouping, we start by grouping the terms in pairs:
\[ (2x^3 - x^2) + (-2x + 1) \]
Next, we factor out the common factors from each group:
-
From the first group \(2x^3 - x^2\), we can factor out \(x^2\): \[ x^2(2x - 1) \]
-
From the second group \(-2x + 1\), we can factor out \(-1\): \[ -1(2x - 1) \]
Now we can combine these factored groups:
\[ x^2(2x - 1) - 1(2x - 1) = 0 \] \[ (2x - 1)(x^2 - 1) = 0 \]
Next, we can further factor \(x^2 - 1\) using the difference of squares:
\[ x^2 - 1 = (x - 1)(x + 1) \]
Thus, we have:
\[ (2x - 1)(x - 1)(x + 1) = 0 \]
Setting each factor equal to zero gives:
-
\(2x - 1 = 0\) \[ 2x = 1 \quad \Rightarrow \quad x = \frac{1}{2} \]
-
\(x - 1 = 0\) \[ x = 1 \]
-
\(x + 1 = 0\) \[ x = -1 \]
Thus, the solutions to the equation \(2x^3 - x^2 - 2x + 1 = 0\) are:
\[ \boxed{\frac{1}{2}, 1, -1} \]